Efeitos do monitoramento sobre a correspondência fazer-dizer em crianças em uma atividade acadêmica - Donaris, Douglas Fernandes (2020)
The line of research that investigates verbal correspondence seeks to analyze the relation between what a person says he has done or will do and what he actually did, as well as its control variables. The present study replicated and extended the experiment by Brino and Rose (2006) and aimed to evaluate the effect of monitoring, that is, the presence or absence of different social agents (adult and child) in children's self-reports on their performance in a reading task. Six children aged between nine and 10 years participated. “Doing” consisted of reading aloud a word that was presented on a computer screen and “saying” consisted of reporting, after hearing an automated computer feedback, whether the reading was correct or not. The procedure was composed by the following experimental conditions: A) Baseline (no monitor), which assessed the levels of correspondence in the absence of social agents and without contingent reinforcement to specific reports; B) Presence of the adult monitor, which investigated whether and to what extent the presence of an adult would affect the accuracy of self-reports, and C) Presence of the child monitor, which was similar to condition B, but the type of social agent who was present in the room during the task changed to a child who was close in age to the participants’. A reversal design (ABACA and ACABA) was used and the results were analyzed based on the percentage of correspondence of reports of errors and successes of the participants throughout the experimental conditions. The results showed that monitoring produced an increase in the correspondence levels of error reports for all participants. Monitoring proved to be a relevant variable in controlling the accuracy of verbal reports. The order of presentation of the two types of monitors did not appear to have any effect on the participants' correspondence levels. There was no difference in the correspondence patterns depending on the type of monitor.